Acceptability of Fruit and Vegetable Marketing Materials for Schools Among Adolescents (P16-043-19). (13th June 2019) - Pisano, Sydney; Adams, Marc; Koester, Kassandra; Bruening, Meg
Abstract: Objectives: It's not well understood how youth perceive existing fruit and vegetable (FV) marketing materials available in schools. This ancillary study sought to assess the acceptability of FV marketing materials freely available to schools among adolescents in grades 6–12. Methods: Middle and high school students ( n  = 40; 50% female; 52.5% Hispanic) in the Phoenix, AZ area were asked to rank marketing materials ( n  = 35) from favorite to least favorite in four categories: table tents, medium posters, large posters and announcements. Favorites were determined by showing participants two items at a time and having them choose which they preferred. Marketing items were initially selected randomly from all items available from various nutrition campaigns and represented a subset of the top-rated items screened by school nutrition professionals. Students participated in a 20–30 minute interview and judged items based on acceptance/attractiveness, comprehension, relevance, motivation and uniqueness of the materials. A content analysis was performed on the items. Results: A content analysis determined 84% of participants chose advertisements that had more than 4 color groups. Participant preference of advertisement length and word count was varied. A total of 5 themes and 20 subthemes emerged when participants discussed their preferences of the FV materials. Themes included: Likes (e.g., colors, length, FV shown), dislikes (e.g., length, FV shown), health information (e.g., vitamin shown), comprehension (e.g., doesn't recognize FV), and social aspects (e.g., peer opinion). Peer opinion often influenced participant opinion on marketing materials. Participants often said peers wouldn't like the advertisements shown: "…kids my age think that vegetables are not good, and they like food more than vegetables." Conclusions: Participants expressed they liked the marketing materials shown. Students preferred advertisements with more color. Word count had minimal influence on their opinions of the marketing materials. Further research needs to be done to determine if there is a link between adolescent preferences on FV marketing materials and FV consumption habits. Funding Sources: This study was supported by a grant from the National Heart, Lung, and Blood Institute of NIH.